A justiça social e a comunidade escolar da EMEF Beija Flor na cidade de Toropi/RS - Nascimento, Thaiane Bonaldo do (2023)
The thesis was developed in the Doctorate course of the Graduate Program in Education at the Federal University of Santa Maria, in the line of research “educational public policies, educational practices and their interfaces - LP2”. The guiding question of the research was: To what extent does a school for the Early Years of Elementary Education in the municipality of Toropi/RS constitute itself as a promoter of Social Justice? The General Objective was listed as “Understand the extent to which a school for the Early Years of Elementary Education in the municipality of Toropi/RS constitutes a promoter of Social Justice”. The research has a qualitative bias of the Case Study type and the instruments used were Documentary Research and Questionnaires. The first instrument was centrality the Pedagogical Political Project, School Regiment, Study Plan and the Municipal Curriculum Guiding Document of the Municipal School of Beija Flor. The questionnaires included the participation of members of the school community, including parents/guardians of 5th year students, employees working in education, 5th year elementary school students, as well as teachers and managers of the institution. The questionnaires were prepared in agreement with the public, so 2 were directed to the group of adult research participants, who answered them via google forms or in print. The students answered 1 printed questionnaire, with the same objectives as the questionnaire directed to the other group of participants. The data obtained through these were treated from the analyzed by Content Analysis according to Franco (2005). To support the theoretical discussions proposed here, a dialogue was held with Fraser (2006; 2003), Paulo Freire (2020, 2011), Miguel Arroyo (2018; 2019), Raewyn Connell (2006), Jurjo Torres Santomé (2014), François Dubet (2019; 2015), Gimeno Sacristán (2017; 2013), among other authors. I defend the thesis that: Curricular Justice and Social Justice demand collective and constant struggles, considering the scope of redistribution, recognition and representation. The school becomes one of the possible spaces for training individuals aware of the emergence of curricular and social changes in favor of Social Justice. It is in this direction that the defense of public schools is essential. It was inferred that EMEF Beija Flor, through public policies, puts into effect the conditions of access, permanence and academic success of students, understanding them as rights and reducing the impact of social inequalities on school. The students highlighted the need to implement Curriculum Justice, recognizing that the culture of minorities and the current processes of oppression must compose the curriculum. Furthermore, it was evidenced that even the participants complaining for spaces of participation in the school environment, they do not materialize. The relationships between power, politics and school management remain correlated, preventing democratic management and, therefore, participatory parity.